Prevalence and Determinants of Unintended Pregnancy in Sub -Saharan Africa: A Systematic Review - (:unkn) unknown (My University, 2020)
Over forty percent of pregnancies worldwide are unintended, with a quarter of these from Africa. There is a growing body of evidence regarding the adverse health, economic, societal, and developmental consequences of unintended pregnancies. The main aim of this systematic review is to report on the current prevalence and determinants of unintended pregnancies in sub-Saharan Africa. A literature search (in PubMed, Embase, PsycINFO and Scopus) was performed up to 29 May 2019. The Joanna Briggs Institute Reviewers' Manual guidelines to assess the quality of peer-reviewed quantitative articles were used to select articles that met our inclusion criteria. A total of 29 articles from 9 countries were included in the final review. The mean unintended pregnancy rate was 33.9%. The mean unwanted pregnancy rate was 11.2%, while the mean mistimed pregnancy rate was 22.1%. Mistimed pregnancies were more frequent across the 13 studies that classified unintended pregnancies into the unwanted and mistimed pregnancy sub-groups. Being an adolescent (19 years old or less), single, and having 5 children or more were consistent risk factors for unintended pregnancy. Awareness and use of modern contraception, level of education, socio-economic status, religion, and area of residence as independent variables were either protective or associated with an increased risk of reporting a pregnancy as being unintended. The unintended pregnancy rate in sub-Saharan Africa remains high, especially among singles, adolescents, and women with 5 or more children. There was no uniform tool used across studies to capture pregnancy intention. The studies did not capture pregnancy intention among women whose pregnancies ended up as stillbirths or abortions. More research is required to ascertain when it is best to capture pregnancy intention, and how exclusion or inclusion of pregnancies ending up as stillbirths or abortions impact reported unintended pregnancy rates.
Keywords: African Research